Joint effect of diabetes and opiate use on all-cause and cause-specific mortality: the Golestan cohort study - Nalini, Mahdi (Int J Epidemiol, 2020)
BACKGROUND: Many diabetic individuals use prescription and non-prescription opioids and opiates. We aimed to investigate the joint effect of diabetes and opiate use on all-cause and cause-specific mortality. METHODS: Golestan Cohort study is a prospective population-based study in Iran. A total of 50 045 people—aged 40–75, 28 811 women, 8487 opiate users, 3548 diabetic patients—were followed during a median of 11.1 years, with over 99% success follow-up. Hazard ratio and 95% confidence intervals (HRs, 95% CIs), and preventable death attributable to each risk factor, were calculated. RESULTS: After 533 309 person-years, 7060 deaths occurred: 4178 (10.8%) of non-diabetic non-opiate users, 757 (25.3%) diabetic non-users, 1906 (24.0%) non-diabetic opiate users and 219 (39.8%) diabetic opiate users. Compared with non-diabetic non-users, HRs (95% CIs) for all-cause mortality were 2.17 (2.00–2.35) in diabetic non-opiate users, 1.63 (1.53–1.74) in non-diabetic opiate users and 2.76 (2.40–3.17) in diabetic opiate users. Among those who both had diabetes and used opiates, 63.8% (95% CI: 58.3%–68.5%) of all deaths were attributable to these risk factors, compared with 53.9% (95% CI: 50%–57.4%) in people who only had diabetes and 38.7% (95% CI: 34.6%–42.5%) in non-diabetic opiate users. Diabetes was more strongly associated with cardiovascular than cancer mortality. The risk of early mortality in known cases of diabetes did not depend on whether they started opiate use before or after their diagnosis. CONCLUSIONS: Using opiates is detrimental to the health of diabetic patients. Public awareness about the health effects of opiates, and improvement of diabetes care especially among individuals with or at risk of opiate use, are necessary.